Synthesis of biodiesel from non-edible (Brachychiton populneus) oil in the presence of nickel oxide nanocatalyst: Parametric and optimisation studies. (September 2021) - Dawood, Sumreen; Koyande, Apurav Krishna; Ahmad, Mushtaq; Mubashir, Muhammad; Asif, Saira; Klemeš, Jiří Jaromír; Bokhari, Awais; Saqib, Sidra; Lee, Moonyong; Qyyum, Muhammad Abdul; Show, Pau Loke
Abstract: The present study defines a novel green method for the synthesis of the nickel oxide nanocatalyst by using an aqueous latex extract of the Ficus elastic . The catalyst was examined for the conversion of novel Brachychiton populneus seed oil (BPSO) into biodiesel. The Brachychiton populneus seeds have a higher oil content (41 wt%) and free fatty acid value (3.8 mg KOH/g). The synthesised green nanocatalyst was examined by the Fourier transform infrared (FT-IR) spectroscopy, energy dispersive X-Ray (EDX) spectroscopy, X-Ray diffraction (XRD) spectroscopy and scanning electron microscopy (SEM). The obtained results show that the synthesised green nanocatalyst was 22–26 nm in diameter and spherical-cubic in shape with a higher rate of catalytic efficiency. It was utilised further for the conversion of BPSO into biofuel. Due to the high free fatty acid value, the biodiesel was synthesised by the two-step process, i.e., pretreatment of the BPSO by means of acid esterification and then followed by the transesterification reaction. The acidic catalyst (H2 SO4 ) was used for the pretreatment of BPSO. The optimum condition for the transesterification of the pretreated BPSO was 1:9 of oil-methanol molar ratio, 2.5 wt % of prepared nanocatalyst concentration and 85 °C of reaction temperature corresponding to the highest biodiesel yield of 97.5 wt%. The synthesised biodiesel was analysed by the FT-IR and GC-MS technique to determine the chemical composition of fatty acid methyl esters. Fuel properties of Brachychiton populneus seed oil biodiesel (BPSOB) were also examined, compared, and it falls in the prescribed range of ASTM standards. Graphical abstract: Image 1 Highlights: Brachychiton populneus seeds possess high oil contents (41%). The optimum condition for transesterification of these seed oil was 1:9 oil-methanol. At optimum conditions highest biodiesel yield of 97.5% was achieved. FT-IR and GC-MS confirmed the synthesise of biodiesel. Populneus possesses significant potential as biodiesel feedstock.